New anthrarobin acyl derivatives as butyrylcholinesterase inhibitors: synthesis, in vitro and in silico studies. Issue 7 (July 2017) - Lateef, Mehreen; Azhar, Abid; Siddiqui, Bina S.; Zarina, Shamshad; uddin, Nizam; Anwar, Muhammad F.; Siddiqui, Kauser; Azhar, Kaniz F.; Iqbal, Lubna; Mehmood, Rashad; Perveen, Shagufta
Abstract: To treat Alzheimer's disease (AD), the available candidates are effective only against mild AD or have side effects. So, a study was planned to synthesis new candidates that may have good potential to treat AD. A series of new anthrarobin acyl derivatives (2 –8 ) were synthesized by the reaction of anthrarobin (1 ) and acetic anhydride/acyl chlorides. The product were characterized by 1 H NMR and EI-MS, and evaluated for butyrylcholinesterase (BuChE) inhibition activity. Compounds5 and4 showed notable BuChE inhibitory potential with IC50 5.3 ± 1.23 and 17.2 ± 0.47 μM, respectively when compared with the standard eserine (IC50 7.8 ± 0.27 μM), compound5 showed potent BuChE inhibition potential than the standard eserine. The active compounds5 and4 have acyl groups at 2-OH and 10-OH positions which may be responsible for inhibitory potential as this orientation is absent in other products. In silico studies of5 and4 products revealed the high inhibitory potential due to stable binding of ligand with the BuChE active sites with docking energy score −18.8779 kcal/mol and −23.1159 kcal/mol, respectively. Subsequently, compound5 that have potent BuChE inhibitory activity could be the potential candidate for drug development for Alzheimer's disease.